Thermal stability of FeSi as barrier layer in high-performance Mg2Si0.3Sn0.7 thermoelectric device - Shanshan Hu; Chen Huang; Changyuan Li; Long Yang; Zhiwei Chen; Baisheng Sa; Wen Li; Yanzhong Pei (Journal of Materiomics)
Thermal stability of thermoelectric devices plays a pivotal role in their practical applications. Chemical reaction/diffusion between thermoelectric materials and electrodes is one of the primary factors contributing to the degradation/failure of device performance at elevated temperatures. Introducing barrier layers to impede the behavior of chemical reactions has emerged as an effective approach for averting the failure of these devices. In this work, the FeSi is revealed to be a potent material of barrier layer in high-performance Mg2Si0.3Sn0.7 thermoelectric material based on the considerations of interfacial reaction energy and sinterability. The well-established bond in Mg2Si0.3Sn0.7/FeSi joint results in a low contact resistivity of ∼20 μΩ⸱cm2 and a conversion efficient of ∼6.5% for the Mg2Si0.3Sn0.7 single-leg device is achieved at a temperature difference of ∼290 K. Long-term measurements of the device at a hot-side temperature of 600 K reveal that the performance remains nearly invariable as time further increases, which suggests that the FeSi layer retards the chemical reaction/diffusion.